Prescribing skill and Medication Error: Role of Pharmacology Teaching - Mainul, Haque; Badar Uddin, Umar (2015)
Medication error is a huge threat to the health care system. It compromises the health of the patients and also caused them financial loss. There have been concerns over medication errors globally. Modern definitions, classifications and recommendations to minimize medication errors have made it much easier to tackle medication errors by the health care professionals, governments, policy makers and other stakeholders. The classification, identification and rates of medication error vary greatly; this made it difficult for researchers to come to a term that is essential for easy detection and prevention of medication errors. Medical education did not give much emphasis on this issue due to the poor curriculum designs. The consequence is lack of knowledge and skills for rational prescribing among medical stu-dents and fresh graduates. Medical students and junior doctors showed their concerns on lack of confidence in pre-scribing safely to avoid medication errors. Among other recommended ways to prevent medication errors and make prescribing processes involving drug use safer, medical education pertaining rational prescribing should be the prime consideration. There is consensus about formulating curriculum in clinical pharmacology and therapeutics and setting new objectives and outcomes for medical students with regards to medication errors. The objectives are set depend-ing on the outcome of the competencies required by future doctors in their practice. The method of assessment in medical schools also need to be improved based on real world situation and by giving more emphasis on the skills needed for prescribing drugs safely and rationally.